치료 불응성 성인형 스틸병 아나킨라 사용 후 임상 호전을 보인 증례 보고 - 오지민; Ji Min Oh; 김형진; Hyung Jin Kim; 이재준; Jae Joon Lee; 안중경; Joong Kyong Ahn; 이유선; You Sun Lee; 고은미; Eun Mi Koh; et al. (The Korean journal of medicine, 2012)
Adult-onset Still`s disease (AOSD) is a systemic inflammatory disorder with variable clinical features. The interleukin (IL)-1 receptor antagonist anakinra has been proposed as an alternative effective treatment in refractory AOSD. We report, for the first time in Korea, two cases of refractory AOSD in which anakinra treatment produced a clinical response. The first patient had frequent clinical flare-ups with fever, sore throat, myalgia, and pleuritic chest pain despite treatment with methotrexate and etanercept. In the second patient, treatments with various immunosuppressive agents failed to control the disease activity. Treatment with anakinra 100 mg/day was initiated in both cases. A complete clinical remission and improvement in the laboratory parameters were observed. The steroid dose was tapered without further clinical flare-ups. Anakinra appears to be an effective alternative treatment modality in patients with AOSD refractory to conventional disease-modifying anti-rheumatic drugs and corticosteroid therapy. (Korean J Med 2012;82:520-524)